Assessing the Impact of Service Quality Dimensions on Customer Satisfaction in Budget Airlines - Kok Ban Teoh; Yee Huei Lok; Lidwina Yi Ming Kee; Xuanting Li; Yinglan Li; Yuxin Li; Zhongkai Liao; Fahad Neyaz; Anees Jane Ali; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
In the highly competitive airline industry, budget carriers must focus on customer satisfaction as a critical strategy to sustain loyalty and differentiation. This study aims to investigate the factors influencing customer satisfaction with AirAsia in Malaysia, specifically examining the roles of price, service quality, food service, assurance, and empathy. A quantitative approach was employed using survey data collected from AirAsia passengers, and regression analysis was conducted to assess the influence of these variables. The results reveal that empathy, assurance, and food service significantly affect customer satisfaction, with empathy emerging as the strongest predictor (? = 0.480, p 0.01). Assurance also demonstrated a positive influence (? = 0.203, p 0.05), followed by food service (? = 0.178, p 0.1). Together, these variables explained 66.1% of the variance in customer satisfaction (R² = 0.661). In contrast, price (? = 0.059) and service quality (? = 0.069) showed no significant impact. These findings underscore the importance of prioritizing empathetic service, trust-building, and food quality enhancements over pricing strategies alone. The study provides both theoretical insights into customer satisfaction determinants in low-cost aviation and practical guidance for airlines seeking to strengthen customer experiences and maintain competitiveness.